The Incremental Prognostic Value of Hepatocyte Growth Factor in First-Ever Acute Ischemic Stroke: An Early Link Between Growth Factor and Interleukins - Li, Fangfang; Liu, Ping; Huang, Yuyou; Li, Lingzhi; Zhang, Sijia; Yang, Zhenhong; Wang, Rongliang; Tao, Zhen; Han, Ziping; Fan, Junfen; Zheng, Yangmin; Zhao, Haiping; et al. (Frontiers in Neurology, 2021)
Hepatocyte growth factor (HGF) is appealing as a prognostic factor for acute ischemic stroke (AIS), here, we sought to validate its earlier predictive accuracy within 24 hours for first-ever AIS. Moreover, HGF interact with interleukins in basic research, drawing their associations may provide novel immunomodulatory therapeutic strategy. First-ever AIS patients (n = 202) within 24 hours were recruited. Plasma HGF and related interleukins concentrations were measured by multiplex immunoassays. The primary outcome was major disability (modified Rankin Scale score ≥3) at 3 months after AIS, and secondary outcome was death. Elastic net regression was applied to screen variables associated with stroke outcome, and then binary multivariable logistic analysis was adopted to explore the relationship of HGF and stroke outcome. After multivariate adjustment, upregulated HGF levels were associated with higher risk of primary outcome (odds ratio, 7.606; 95% CI, 3.090-18.726; p<0.001). Adding HGF to conventional risk factors significantly improved the predictive power for unfavorable outcomes (continuous NRI 37.13%, p<0.001; IDI 8.71%, p<0.001). AUC value of traditional model was 0.8896, which reached 0.9210 when HGF was introduced into the model. Elevated HGF may also be a risk factor of mortality within 3 months post-stroke. Besides, HGF level was positively correlated with IL-10 and IL-16, and HGF prior to all interleukins markedly negatively correlated with lymphocyte/neutrophil ratio. HGF within 24 hours may have prognostic potential for AIS, and what we found reinforce the link between HGF and interleukins, and intervention of HGF may offer an immunomodulatory therapeutic target for AIS.